The impact of neuropsychological assessment in epileptic focus localization - Malobabić Marina (Medicinski fakultet Priština, Društvo lekara Kosova i Metohije Srpskog lekarskog društva, 2021)
Introduction: Epilepsy that takes place in the temporal lobe is manifested through three symptoms: aura, temporal pseudoabsence and automatisms, while right-sided temporal lobe epilepsy had been also linked with visual or image learning and memory deficits. Case outline: Patient 24 years old in 2020. In July 2020 had complex partial seizures with an unordinary psychomotoric reactions and verbalization, followed by qualitative conscience change in the form of confusion and amnesia. Therapy with paroxetine showed no result. Neuropsychological evaluation showed no other cognitive deficit than severe visuoconstruction dyspraxia and discrete decrease in complex attention. In behavioral aspect prodromal symptoms of tension, anxiety and depression were occurred. Conclusion: Neuropsychological assessment is, along the magnetic resonance imaging and electroencephalographic, the most important method for indicating cognitive deficit in epilepsy and determining the epileptic focus.